A business privacy model for virtual communities. (23rd March 2009) - Yassine, Abdulsalam; Shirmohammadi, Shervin
Virtual communities in online networks have created unprecedented opportunities for consumer cooperation, which, naturally, impacts business functions significantly. While virtual communities are now formed for almost every field of life that one could imagine, they still lack a business model by which consumers can make the most of their private data and presumed privacy rights. This paper proposes a business privacy model for virtual communities based on allowing consumers to capitalise on the value of their personal information and get something of value in return. The proposed business model employs a privacy risk quantification mechanism, a game theoretic negotiation protocol and a risk-based premium to determine the consumers' payoff.